2019
DOI: 10.3390/vaccines7020037
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Plasmid DNA and mRNA as Vaccine Technologies

Abstract: This review provides a comparison of the theoretical issues and experimental findings for plasmid DNA and mRNA vaccine technologies. While both have been under development since the 1990s, in recent years, significant excitement has turned to mRNA despite the licensure of several veterinary DNA vaccines. Both have required efforts to increase their potency either via manipulating the plasmid DNA and the mRNA directly or through the addition of adjuvants or immunomodulators as well as delivery systems and formu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
315
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 330 publications
(323 citation statements)
references
References 91 publications
(121 reference statements)
0
315
0
8
Order By: Relevance
“…DNA vaccines are typically comprised of plasmid DNA molecules that encode one or more antigens. They are superior to mRNA vaccines in the formulations needed for stability and delivery efficiency, nevertheless they need to enter the nucleus that may bring in the risk of vctor integration and mutations in the host genome [48]. So far, two SARS-CoV-2 DNA vaccines are under development.…”
Section: Dna Vaccinementioning
confidence: 99%
“…DNA vaccines are typically comprised of plasmid DNA molecules that encode one or more antigens. They are superior to mRNA vaccines in the formulations needed for stability and delivery efficiency, nevertheless they need to enter the nucleus that may bring in the risk of vctor integration and mutations in the host genome [48]. So far, two SARS-CoV-2 DNA vaccines are under development.…”
Section: Dna Vaccinementioning
confidence: 99%
“…Even though, in a recent overview of prophylactic and therapeutic DNA and mRNA vaccine studies, it was shown that in some studies, up to 78% of vaccinated subjects experienced adverse events, amongst which 10% were of grade 3. None of the discussed trials that involved mRNA have reached phase 3 research stages yet [27]. Follow-up was given to the notification of the erroneous study product following good clinical practice guidelines, amongst which were notification of participants, competent authorities and institutional review boards.…”
Section: Discussionmentioning
confidence: 99%
“…Besides the general advantages of mRNA, previously mentioned, this active substance shows specific interesting features for immunotherapy: The immunostimulatory capacity, although it can also have potential toxicity, the transient nature of the antigen and the versatility of applications, including prophylaxis, therapy and personalized vaccines [164,165]. Several preclinical studies of mRNA vaccines are showing promising perspectives.…”
Section: Immunotherapymentioning
confidence: 99%
“…However, the preclinical and human immunogenicity is not always the same, animal studies are not predictive of human efficacy, and there is a lack of knowledge about the targets and type of immune responses which are essential for effective therapy. These challenges highlight the need to carry out further studies on the correlation between the immune response mechanisms in animals and in humans, as well as of a better understanding of the diseases to be treated or prevented, for the clinical success of immunotherapy [14,165].…”
Section: Immunotherapymentioning
confidence: 99%
See 1 more Smart Citation